Від трубадурів до неокласиків: формалістична тенденція європейської поезії - Левчук, Тереза; Levchuk, Tereza (Східноєвропейський національний університет імені Лесі Українки, 2013)
Простежено формалістичну тенденцію в європейській поезії. З’ясовано, що відточеність віршованих форм культивувалася у творчості провансальських трубадурів, поетів «нового солодкого стилю», петраркістів, учасників групи «Плеяда», класицистів та преціоністів, митців угруповання «Парнас», символістів та українських неокласиків. Визначальними ознаками віршотворчості названих митців є ідеалістична настанова, технічна майстерність, вишуканість поетичних засобів. Заслуга полягає у збагаченні літературно-поетичної мови.It was traced the formalist tendency in European poetry and was found that the elegance of poetic forms cultivated in the work of Provençal troubadours, poets of the «new sweet style», petrarkists, members of the poetry group «Galaxy», classicists and representatives of pretiosus, paintings of «Parnassus», the Symbolists and Ukrainian neoclassical poets. Their versification determine the idealistic description the beauty of nature and love, technical skill, the appropriateness of poetic means. The achieve of formalist poets in enriching literary and poetic language, the development of new forms of genre, complication rate and rhymes are undeniable. Etiquette became motivation to formalistic perfection for the troubadours, poets of «new style» and petrarkists; representatives of groups «Pleiades» and «Parnassus» (as well as classicists in era of absolute monarchies) focused on the rationality of ancient aesthetic ideal; aestheticism was a defining criterion of aspirations for the Symbolists and the neoclassics of the twentieth century.
From the troubadours to the neoclassical: the formalist tendency of European poetry
Keywords: форма; зміст; жанр; ритм; рима; досконалість; form; content; genre; rhythm; rhyme; perfection